A Validated Mathematical Model of the Cytokine Release Syndrome in Severe COVID-19 - Reis, Ruy Freitas; Pigozzo, Alexandre Bittencourt; Bonin, Carla Rezende Barbosa; Quintela, Barbara de Melo; Pompei, Lara Turetta; Vieira, Ana Carolina; Silva, Larissa de Lima e; Xavier, Maicom Peters; Weber dos Santos, Rodrigo; Lobosco, Marcelo (Frontiers in Molecular Biosciences, 2021)
By June 2021, a new contagious disease, the Coronavirus disease 2019 (COVID-19), has infected more than 172 million people worldwide, causing more than 3.7 million deaths. Many aspects related to the interactions of the disease's causative agent, SAR2-CoV-2, and the immune response are not well understood: the multiscale interactions among the various components of the human immune system and the pathogen are very complex. Mathematical and computational tools can help researchers to answer these open questions about the disease. In this work, we present a system of fifteen ordinary differential equations that models the immune response to SARS-CoV-2. The model is used to investigate the hypothesis that the SARS-CoV-2 infects immune cells and, for this reason, induces high-level productions of inflammatory cytokines. Simulation results support this hypothesis and further explain why survivors have lower levels of cytokines levels than non-survivors.